The effect of breathing exercises on adults' sleep quality: an intervention that works - Steinmane, Valērija; Fernate, Andra (Frontiers in Sleep, 2025)
This study investigates the application of various breathing exercises to enhance sleep quality. Respiration is an indispensable aspect of life that significantly influences both the physical and mental wellbeing of individuals, as well as sleep quality. Embracing appropriate breathing exercises has proven to be advantageous for short-term relief and long-term holistic health. The aim of the study is to theoretically investigate the application of breathing exercises to improve sleep quality. Scientific article review was conducted, drawing upon completed trials within scientific articles found in ScienceDirect, PubMed and Scopus databases (period 2000–2024). The focus on articles that utilize deep breathing, diaphragmatic breathing, mindful breathing, respiratory muscle training, and pursed lip breathing allowed us to explore the potential benefits of these techniques on sleep quality. By synthesizing findings from diverse trials, this study contributes to a deeper understanding of how specific breathing techniques may modulate physiological and psychological factors involved in sleep regulation. The durations of adult engagement in daily breathing exercise sessions lasted for a month or longer. Study results show that consistent success was observed across seven studies employing various breathing exercises for distinct patient groups, with improved sleep quality noted among participants who completed the prescribed breathing techniques. The insights gained from this theoretical investigation promote knowledge for an intervention (content, duration, timing) that works and improves sleep quality through the approach of breathing exercise application.